Sea Nono Heu dan Martabat Wanita dalam Tradisi Perkawinan Adat Masyarakat Suku Amarasi di Timor - Moses Kollo; Yanrini Martha Anabokay; Diana Rohi (Universitas Galuh, 2023)
Sea Nono Heu. Sea Nono Heu is a custom in traditional marriage owned by the Amarasi Tribe community in Timor, East Nusa Tenggara region. This study aims to describe